The Exile Experience Reconsidered: a Comparative Perspective in European Cultural Migration during the Interwar Period - Renato Camurri (Transatlantica)
This paper deals with exile in the 20th century and makes some suggestions for a reconsideration of this experience. The reasons for its peculiarity lie in a series of political, religious, racial and moral elements but when we speak of exile we are implicitly referring to substantially different experiences and phenomena: social exile, political exile and intellectual exile.The historiography of cultural migration has been through new and important developments over the past twenty years, developments that have enlarged the field across the borders of where sector-based studies grew. The first phase of studies into intellectual exile was strongly conditioned by two classic interpretative paradigms: the acculturation paradigm and the paradigm of the impact refugee scholars had on American culture. However, the field of so called “Exile Studies” has widened remarkably in recent years extending to philosophy, literature, sociology and anthropology. This has provoked a series of negative effects, such as an excessive generalization of the concept of exile and the loss of the historical specificity of this phenomenon.The author analyzes some features of the experience of Italian exiles in the United States starting from a comparative approach. His aim is to highlight major differences between various national cases (German, French and Italian). He concludes that the meaning of exile in the 20th century essentially indicates an experience of fracture, of displacement from the motherland, of alienation lived as a loss, of injury.